(untitled) (Research, Society and Development, 2023)
The experiment was carried out with the objective of evaluating the effect of vitamin C supplementation on performance, biometry of the heart, digestive and lymphoid organs, histomoformometry of the cloacal pouch and carcass yield and prime cuts of broiler chickens from 1 to 45 days old, naturally subjected to cyclic heat stress. Four hundred Cobb broiler chickens were used in a completely randomized experimental design, with five treatments: 0; 100; 200; 300; 400 ppm of vitamin C in the feed. In the period from 1 to 21 days of age, treatments influenced weight gain, however, there was no effect of treatments on feed intake and feed conversion of birds. In the phase from 1 to 45 days of age, it was verified that the treatments had a quadratic influence on the feed conversion, which improved up to the estimated level of 206.19 ppm of vitamin C in the diet. Supplemented vitamin C levels influenced carcass and drumstick yields. However, there was no effect of the treatments on the biometry of the digestive and lymphoid organs, in addition to the fact that there was no influence on the histomorphometry parameters of the cloacal pouch of heat-stressed broilers. Diet supplementation with vitamin C improves zootechnical performance and carcass yield in heat-stressed broiler chickens.